(untitled) (Research, Society and Development, 2020)
Through this study, we sought identify the technological tools used in the teaching and learning process in the face of the COVID-19 pandemic at a public university in the state of Ceará. For data collection, exploratory research was carried out, using semi-structured questionnaires through Google forms. 126 people were interviewed, of which 32 are teachers and 96 students. According to the answers given by the students, 86% have Wi-Fi at home. The rest use internet using mobile data or from neighbors’ homes. Regarding the tools used, 95% of students use Smartphones, while 53% indicated the notebook, 6% the computer and only 1% use the TV. Google meet was identified as the most used app in class. Among teachers, most reported having Wi-Fi at home and the main tools used are smartphones, notebooks, computers and a minority reported using tablets. According to the teachers’ responses, 73% send material to students as a form of interaction. 67% record the classes and send them, while 64% do video conferencing. Most respondents, including teachers and students, mentioned that face-to-face classes are more effective in the teaching and learning process. Thus, it is noted that, despite the efforts of the academic staff to continue teaching activities during the health crisis, much progress is still needed in the education institution with regard to the inclusion of technologies in the processes educational.